The implementation of queuing theory for the optimization of service counter case study of Pos Malaysia Berhad - Rabiatul Nabila Che Johar
Today, everything is about on what is posted on the internet. Life evolved around it and people search and gets information from the internet. Thus, when a negative comments and feedbacks were posted on the internet, it is important that the businesses respond to it as quickly as possible. Pos Malaysia Bhd. has been receiving negative comments on their social media and other consumer platform such as Aduan Rakyat and Kementerian Komunikasi dan Multimedia Malaysia. One of the most frequent comments made is about the insuffieciency of their service counter. This paper in estigate the complaints by observing one of its busiest branch which located at Wangsamaju. Based on the data gathered, the waiting time in this branch exceeded 10 minutes waiting time that customer prefer. In fact, on the busiest day of the week, the queue is so long that the waiting time for each customer reach one hour. The data is run in a QM for Windows application and the research suggested that Pos Malaysia Wangsamaju branch to use one of it 'Kaunter Poslaju' as 'Kaunter Pelbagai' in order to reduce the waiting time.